Comparison of a ready-to-use intranasal dexmedetomidine spray with traditional intranasal dexmedetomidine drops for sedation in preschool children: a prospective, randomized, controlled study - Qi-Qi Jin; Wei-Cha Cai; Ying-Feng Zhou; Yan-Tong Zhang; Gang Chen; Meng-Ting Xu; Jun Li; Kai-Ming Yuan (Frontiers in Pharmacology)
PurposeThis study compared the efficacy and acceptability of a ready-to-use intranasal dexmedetomidine spray (DS) versus traditional drops administered by syringe (DD) in pediatric patients undergoing elective surgery.Patients and MethodsEighty-six preschool children were enrolled in a prospective, randomized, controlled study. Children were randomly assigned to receive either DS or DD. For children weighing between 10.5 and 18.5 kg, a dexmedetomidine dosage of 30 μg (two sprays) was administered, while those weighing between 18.5 and 25.5 kg received 45 μg (three sprays). In the DD group, dexmedetomidine was administered at a dose of 2 μg/kg based on body weight. The primary outcome was the proportion of children achieving a Ramsay sedation scale (RSS) score of ≥3 within 30 min. Secondary outcomes included acceptance of intranasal medication, anxiety at parental separation and prior to induction, and compliance with induction.ResultsA total of 83 cases were analyzed. The proportion of children achieving an RSS score of ≥3 within 30 min was similar between the DS and DD groups (90.7% vs. 77.5%, respectively). However, the acceptance score was significantly better in the DS group (mean difference [95%]: −0.9 [−1.267 to −0.5325], P < 0.001). No significant differences were observed between the groups in terms of successful child-parent separation (88.4% vs. 85%) or satisfactory anxiolytic effect prior to induction (95.3% vs. 92.5%). Compliance with induction was comparable, with 53.5% in the DS group and 40.0% in the DD group demonstrating “optimal” compliance.ConclusionBoth intranasal spray and syringe drop methods were highly effective in providing sedation and anxiolysis, but the ready-to-use intranasal dexmedetomidine spray was more acceptable to children, offering a viable alternative to the syringe method.Clinical Trial RegistrationChiCTR.org.cn, identifier ChiCTR2400089374.